Application of kinetics and computational fluid dynamics in pinene isomerization - Xiang, Jionghua; Zhu, Litao; Luo, Zhenghong (Chinese journal of chemical engineering, 2020)
A reliable kinetic model to describe the effects of various factors on the reaction rate and selectivity of pinene isomerization is developed. Furthermore, computational fluid dynamics (CFD) is applied to simulate the solid–liquid dispersion in reactor. The catalyst TiM is obtained by improving the composition and structure of hydrated titanium dioxide. The kinetic equation of pinene isomerization is deduced based on reaction mechanism and catalyst deactivation model. The kinetic equation of pinene isomerization reaction is fitted, and the results show that the fitted equation is correlated with the experimental data. The rate and selectivity of pinene isomerization reaction are affected by the amount of catalyst, deactivation of catalyst, structure of catalyst, reaction temperature and water content of catalyst. The solid–liquid distribution of the reactor is calculated by computational fluid dynamics numerical simulation, and the solid–liquid dispersion in commercial scale reactor is more uniform than that in lab-scale reactor. [Display omitted] •Establish a more complete kinetic model by introducing deactivation model•The kinetic model correlates well with experimental data.•The lab-scale reactor and commercial scale reactor are investigated by CFD numerical simulation.•The factors affecting the rate and selectivity of the pinene isomerization reaction are systematically studied.